2019
DOI: 10.1101/587501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human DNA-PK activates a STING-independent DNA sensing pathway

Abstract: Detection of intracellular DNA by the cGAS-STING pathway activates a type I interferon-mediated innate immune response that protects from virus infection and can be harnessed to promote anti-tumor immunity. Whether there are additional DNA sensing pathways, and how such pathways might function, remains controversial. We show here that humans -but not mice -have a second, potent, STINGindependent DNA sensing pathway that is blocked by the E1A viral oncogene of human adenovirus 5.We identify human DNA-PK as the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 50 publications
4
14
0
Order By: Relevance
“…In contrast, a low dose of 2-Gy irradiation, which induced less DNA damage and restored micronuclei formation and inflammatory signaling in MCF10A XRCC4 KO cells (Figures S1C and S1D). This observation is consistent with a model in which c-NHEJ deficiency impairs cell cycle progression as a consequence of excessive DNA damage after 10 Gy, rather than through the putative role of c-NHEJ factors (i.e., DNA-PK) in pattern recognition (Burleigh et al, 2020;Ferguson et al, 2012;Zhang et al, 2011). We further analyzed inflammatory gene expression in genetically defined MCF10A cells.…”
Section: Cdk1 or C-nhej Inhibition Suppresses Dnadamage-induced Inflammatory Signaling And Anti-tumor Immune Responsessupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, a low dose of 2-Gy irradiation, which induced less DNA damage and restored micronuclei formation and inflammatory signaling in MCF10A XRCC4 KO cells (Figures S1C and S1D). This observation is consistent with a model in which c-NHEJ deficiency impairs cell cycle progression as a consequence of excessive DNA damage after 10 Gy, rather than through the putative role of c-NHEJ factors (i.e., DNA-PK) in pattern recognition (Burleigh et al, 2020;Ferguson et al, 2012;Zhang et al, 2011). We further analyzed inflammatory gene expression in genetically defined MCF10A cells.…”
Section: Cdk1 or C-nhej Inhibition Suppresses Dnadamage-induced Inflammatory Signaling And Anti-tumor Immune Responsessupporting
confidence: 88%
“…Loss of c-NHEJ prevented anti-tumor immune re-sponses in syngeneic melanoma models treated with radiotherapy and immune checkpoint blockade. Although c-NHEJ components DNA-PKcs and KU have been reported as DNA sensors for innate immunity (Burleigh et al, 2020;Ferguson et al, 2012;Zhang et al, 2011), we observed similar reductions in cells that have lost end ligation factors XRCC4 and Lig4, (Graham et al, 2016). XRCC4 and LIG4 are not required for DSB end recognition or signaling, making them unlikely candidates for Article ll OPEN ACCESS pattern recognition.…”
Section: Discussionsupporting
confidence: 50%
“…Interaction between DNA-PKcs and the progenome of the Human Immunodeficiency Virus (HIV) retrovirus has also been shown, although the link to inflammation is unexplored ( 65 ). Interestingly, some DNA viruses have evolved proteins that counteract DNA-PKcs-dependent detection ( 20 ) while others hijack NHEJ to the benefit of their replication ( 66 ), highlighting the tight interplay between viral life cycles and DDR ( 67 ). Yet, there is as of today, limited knowledge concerning the ways in which DNA-PK-dependent inflammatory responses, IFI16- and cGAS-dependent STING activation are orchestrated.…”
Section: Cytosolic Nucleic Acid Detection: Sting As a Central Signaling Hubmentioning
confidence: 99%
“…Indeed, whether DNA-PK requires STING for production of Interferons remains debated ( 18 , 20 , 68 ) ( Figure 1C ). It was reported that DNA-PKcs is recruited to dsDNA in the cytoplasm of both human and murine cells through KU80, triggering IRF3-dependent inflammatory responses ( 18 ).…”
Section: Cytosolic Nucleic Acid Detection: Sting As a Central Signaling Hubmentioning
confidence: 99%
“…However, recent work has questioned this paradigm. Indeed, it has been reported that the DNA-PK DNA repair pathway can operate in the detection of cytosolic dsDNA in human cells, while such DNA-PKdependent IFN production is not witnessed in murine cells [45]. inflammasome inhibits the cGAS-STING pathway [47].…”
Section: I3 Sting-independent Signaling Cross Talks and Regulatory mentioning
confidence: 99%